LINGUOCULTURAL DIMENSION OF THE PHILOSOPHY OF COSMISM - Антіпова, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. The article is devoted do research of the key means specificity, which gives the ideological foundations of the cosmic philosophy a peculiar universality, the ability to express their potential in the context of globalization transformations, the linguocultural space. Aim and tasks: the publication aims are to highlight the linguistic and cosmic philosophy cultural dimension, which implies a number of tasks implementation, such as: do research of the specificity of the thinking processes as a natural manifestation of their adaptation to changes of the planetary nature; revealing the philosophizing specifics as special style determinants of thinking associated with the principles researching of the planetary information space order-ing; determining the personality role in the linguistic and cultural practices of comprehension of the Universe. Research methods: the methodologi-cal tools consist of the sociocultural approach, methodological principles of systemacity and completeness, as well as the method of cultural-semantic analysis. Research results. Under the research a cosmic ideas high potential are established, which are capable the traditional strategy of development modernizing, and, therefore, confronting the civilization crisis. Under these conditions, the linguocultural aspect take on particular im-portance, as indicated by several factors. Firstly, the scope expansion of thought as a globalization attribute of naturally implies the volume expan-sion of the speech. Secondly, nowadays the language primarily is perceived as a means of establishing an inter-civilization dialogue capable of developing an acceptable platform for coexistence for all. Thirdly, the person attempt to comprehend the Universum, in fact, only in the linguistic-cultural plane can be realized. Discussion. Following the ideas of cosmists analysis through the linguistic-cultural component prism results that broadly complement the conceptual gains of researchers in the context of present globalization transformations are obtained. Conclusion. The precondition for the world global image formation is the philosophical guides transformation, systems and means of sensory-forming processes is proved. This is facilitated by the cosmists thinking specifics, which can show a high adaptability degree. These processes by the formation of a fun-damentally new type of a speaker are accompanied – the cosmic-planetary type personality as a holistic and creative subject of culture.